2019
DOI: 10.1124/dmd.119.086678
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Hepatic and Intestinal Metabolism to the Disposition of Niclosamide, a Repurposed Drug with Poor Bioavailability

Abstract: Niclosamide, an antiparasitic, has been repositioned as a potential therapeutic drug for systemic diseases based on its antiviral, anticancer, and anti-infection properties. However, low bioavailability limits its in vivo efficacy. Our aim was to determine whether metabolic disposition by microsomal P450 enzymes in liver and intestine influences niclosamide's bioavailability in vivo, by comparing niclosamide metabolism in wild-type, liver-Cpr-null (LCN), and intestinal epithelium-Cpr-null (IECN) mice. In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
0
23
1
Order By: Relevance
“…27 Moreover, niclosamide was found as a broad-spectrum antiviral against multiple viruses including SARS Cov-2, the causative agent of the current COVID-19 pandemic. 28 Unfortunately, niclosamide did not show appreciable in vivo antiviral efficacy toward ZIKV (data not shown), possibly due to its poor pharmacokinetic properties 26,29 In this work, we screened a small library of niclosamide derivatives. We found that one derivative, JMX0207, showed improved efficacy in the inhibition of the NS2B-NS3 interaction, better inhibition of viral protease function, and enhanced antiviral efficacy in the cell-based antiviral assay, compared to niclosamide.…”
mentioning
confidence: 99%
“…27 Moreover, niclosamide was found as a broad-spectrum antiviral against multiple viruses including SARS Cov-2, the causative agent of the current COVID-19 pandemic. 28 Unfortunately, niclosamide did not show appreciable in vivo antiviral efficacy toward ZIKV (data not shown), possibly due to its poor pharmacokinetic properties 26,29 In this work, we screened a small library of niclosamide derivatives. We found that one derivative, JMX0207, showed improved efficacy in the inhibition of the NS2B-NS3 interaction, better inhibition of viral protease function, and enhanced antiviral efficacy in the cell-based antiviral assay, compared to niclosamide.…”
mentioning
confidence: 99%
“…So, the results of niclosamide inhalation powder and those concentrations above the limit of quantification support the idea of once-daily administration. This may be attributed to an extended residence time in the lung resulting from the avoidance of the extensive first-pass effect that niclosamide undergoes after oral administration [37]. Despite the fact that some drug remains in the plasma, it is reasonable that niclosamide does not accumulate in the lungs following three consecutive days of daily dosing as supported by the low concentrations measured in the lung tissue (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, viral replication can be inhibited by NIC, preventing their further maturation in the host cells [ 19 ]. However, NIC can undergo faster metabolism in liver as glucuronic acid-NIC metabolite by cytochrome P450 enzymes [ 20 ]. Therefore, it is required to have drug delivery carrier to release encapsulated NIC molecules in a sustained manner to delay the metabolism by glucuronidation in liver and/or intestine in a tricky way.…”
Section: Introductionmentioning
confidence: 99%